Riparian Communities along Longitudinal Gradients in Mexico's Northeastern San Juan River - Guerra, San Juana; Lizárraga Mendiola, Liliana; Návar, José (Tecnología y ciencias del agua, 2016)
This research was conducted in three major tributaries of Mexico's northeast San Juan River with the major objectives of: (a) describing the diversity-abundance of riparian trees, benthic insects and fish faunal communities and (b) associating the fish and benthic insect communities to riparian tree communities, flow quality, and discharge parameters along a longitudinal gradient of water stress. Regardless of the high spatial variability, two gradients could be identified using multivariate analysis. Diversity of riparian trees, benthic insects and fish fauna was larger in more pristine and less perturbed upper in contrast to lower sampling sites. Bentic insect diversity was reduced and xerophitic riparian trees are colonizing lower sampling sites due in part to a larger biomass accumulation on rivers, higher stream temperatures and deteriorated river flow quality and diminished streamflow quantity. Benthic insects appear to be better adapted than fish fauna or riparian tree communities to river flow quality and quantity variability. The description and collection of riparian fish, benthic insects and riparian tree communities; as well as the ecological roles between biological groups are an important benchmark source of information and make this report useful to understand potential inherent sources of spatial and temporal variations of riparian communities.